The effect of feeding black soldier fly larvae on growth performance, protein, and fat content of red hybrid tilapia (Oreochromis spp.) - H. N., Aisyah; Z. A. R., Athirah; W. R., Hanani; S. S., Arshad; H. A., Hassim; M. F., Nazarudin; Md Yasin, Ina-Salwany (Veterinary World, 2022)
Background and aim: In the aquaculture industry, the crucial goal is to minimize production costs, especially feeding costs, without significant side effects. Black soldier fly larva (BSFL) is a locally available, eco-friendly, and sustainable source that is high in crude protein (42% dry matter [DM]) and fat (35% DM). This study aimed to determine the growth performance along with the composition of crude fat and protein in red hybrid fingerlings after the addition of BSFL into the diet. Materials and methods: A total of 120 fingerlings of uniform size (mean initial weight of 1.46 ± 0.06 g) were randomly assigned to one of four groups (n = 10) (A, B, C, and D) per tank (1 m × 2 m × 1 m). For 21 days, Group A (control group) was fed with 100% commercial diet; Group B was fed with 90% commercial fish diet + 10% BSFL; Group C was fed with 80% commercial fish diet + 20% BSFL; and Group D was fed with 70% commercial fish diet + 30% BSFL. Feed efficiency, growth performance, and proximate composition analysis were performed on the fish. Results: The results displayed that the group with the highest BSFL percentage had a greater effect on protein and fat composition than the control group. The proximate composition analysis of fish-fed diet revealed that an increase in the level of BSFL inclusion increases the protein content in the fish. In comparison to the other groups, the experimental diet with 30% BSFL inclusion has the highest levels of crude protein (80.30% DM) and fat (2.90% DM). Conclusion: It is concluded that incorporating BSFL into a commercial diet for red hybrid tilapia fingerlings increased crude protein and fat composition, providing an alternative protein and fat source in fish diets.